Determinasi Inovasi Pelayanan Publik Terhadap Konseptualisasi Paradigma Humanis - Rifai Rifai (Cakrawala Repositori IMWI, 2023)
This paper aims to explain the implementation of public services today from a humanistic perspective/paradigm. Public policy innovation as a necessity in principle and substantively will provide reinforcement in responding to and resolving public policy problems that take place in the community.The method used is descriptive method, which describes several studies, public service policies from various literatures. The results of the literature review show that character education and the inculcation of humanistic values to service providers (government/political elites, bureaucratic apparatus) are very important and must be carried out so that the public service process can be of higher quality and provide optimal satisfaction for service recipients.The result to be achieved in this research is the existence of public policy innovation efforts with the dimensions of novelty and usefulness so that it is expected to have an impact on more concrete efforts and build sustainable community participation. Innovation is applied not only at the evaluation stage of public policies but is applied from the beginning of public policy planning, implementation and evaluation of public policies.